Relationship between Lower Urinary Tract Dysfunction and Clinical Features in Chinese Parkinson’s Disease Patients - Duo Xu; Shunchang Han; Jue Wang; Juan Feng (Parkinson's Disease)
Background. Lower urinary tract (LUT) dysfunction is very common in Parkinson’s disease (PD) patients. However, the number of studies conducted on LUT dysfunction and its related factors in Chinese PD patients is very limited, and there is no international consensus concerning the results. Methods. This cross-sectional study enrolled 100 Chinese PD patients. The patients were classified based on their overactive bladder symptom score (OABSS) and then assigned to either a PD with overactive bladder (PD-OAB) group or a PD with no overactive bladder (PD-NOAB) group. A binary logistic regression analysis was performed to identify the accompanying factors for overactive bladder (OAB). Next, correlations between the OABSS and patient sex, age, age of onset, disease duration, MDS-UPDRS-III, H-Y stage, PD subtype, treatment, education, and nonmotor symptoms were analyzed to identify factors correlated with LUT dysfunction. Results. Eighty nine (89%) of the PD patients suffered from LUT dysfunction, and OAB was diagnosed in 45 (45%) of those PD patients. The most common lower urinary tract (LUT) symptom in the PD patients was nighttime frequency (86%), followed by urgency (50%), urge incontinence (34%), and daytime frequency (17%). Patients in the PD-OAB group had an older age and age of onset, were at a more advanced Hoehn–Yahr stage, and had more severe motor symptoms and nonmotor symptoms, including worse cognition, and a greater incidence of REM sleep behavior disorder (RBD). A binary logistic regression analysis showed that a lower Frontal Assessment Battery (FAB) score, higher H-Y stage, and RBD accompanied with a higher prevalence of OAB in PD patients. A multiple linear regression analysis showed that the OABSS was significantly influenced by the FAB score, H-Y stage, RBD, and age. Conclusions. The FAB score, H-Y stage, and RBD are accompanying factors for OAB. A higher OABSS in PD patients was related to a lower FAB score for frontal lobe executive dysfunction, a higher H-Y stage for severity of motor disorders, RBD, and an older age.